El origen de una élite negociante en Madrid : los mercaderes de lonja franceses en el siglo XVII - Ramos Medina, María Dolores (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 2001)
El objeto de este artículo es analizar las empresas francesas en Madrid en el siglo xvii. En primer lugar, presentamos una aproximación a la tipología mercantil. En segundo lugar, estudiamos la estructura empresarial que revela el afianzamiento del capital comercial galo en Madrid a través de una compleja red entre Madrid y los diferentes lugares de Europa. Finalmente, analizamos las redes comerciales y financieras que la burguesía mercantil francesa despliega desde Madrid. The aim of this article is to analyse the french associative pacts within the commerce and finances throughout the 17th century in Madrid. First of all, this article tries to charaterize the social and economic group dedicated to trade and business in order to situate these merchands in the urban hierarchy in Madrid. Many of them were invested in many economic activities. Special attention is paid to the identification of French merchants active in the export of wool to Europe (in particular, France and Flanders) Borne information is given about their economic wealth, and it is proved that they were much less rich than the members of the noble oligarchy in Madrid. Their negotiations and commercial activities were developped into the setting of a complex between Madrid and different places in Europe.